Silica-supported vanadium complexes: Structure, characterization and reactivity, especially towards olefins - Taha, Ziyad Ahmed (University of Ottawa (Canada), 2004)
This thesis is divided into four major parts. The first part describes a simple method to measure the content of reactive hydroxyls of various amorphous silicas before and after thermal treatment. The reaction of excess VOCl3 vapor with surface OH groups of partially dehydroxylated silica is rapid and quantitative. Regardless of the degree of dehydroxylation, the stoichiometry of the reaction is invariable, as demonstrated by 51V magic angle spinning NMR spectroscopy and X-ray absorption spectroscopy (XAS). Using this method, we have quantified the reacive hydroxyls of fumed and precipitated silicas as a function of temperature. Non-porous Aerosil silicas have hydroxyl contents that decrease linearly with increasing temperature of thermal treatment. Porous Sylopol silicas have higher hydroxyl contents per unit surface area than Aerosil silicas treated at the same temperature. The second part deals with characterization of silica-supported vanadium complexes using XAS. A combination of X-ray absorption fine structure (EXAFS) and X-ray-absorption near edge structure (XANES) has been used to characterize the local structure around the vanadium metal center for a series of silica-supported vanadium complexes prepared at various temperatures and on different supports (Aerosil and Sylopol silicas). XAS spectra of all the materials were very similar. The local structure around vanadium was not affected by the thermal treatment and the kind of support. Vanadium has a formal oxidation state of +5 and pseudotetrahedral coordination geometry. The third part deals with the preparation and characterization of new vanadium-based Ziegler-Natta catalysts. The catalysts were prepared by sequential reaction of volatile VOCl3 and trimethylaluminum (TMA) with silica. They were characterized by infrared spectroscopy (IR), electron spin resonance spectroscopy (ESR) and stoichiometric analysis. The interaction of TMA with silica/VOCl3 and silica/TMA/VOCl3 results in the grafting of two AI per original hydroxyl group with concomitant formation of two equiv. CH4. In contrast, the reaction of VOCl3 with silica/TMA results in the grafting of two V per original OH group with concomitant formation of two equiv. CH3Cl. The last part of this thesis describes the reaction of the new vanadium-based Ziegler-Natta catalysts with ethylene, propylene and ethylene-propylene mixture. Kinetics at the gas-solid interface were monitored by in situ IR spectroscopy. The reaction is first order in olefin and first-order in vanadium. Based on kinetics and isotope effects, a mechanism of migratory insertion of the olefin into a vanadium-carbon-alpha-bond (Cossee mechanism) is proposed for the propagation step.
Keywords: Chemistry, Inorganic.; Chemistry, Organic.